IRF7 Regulates TLR2-Mediated Activation of Splenic CD11c(hi) Dendritic Cells - Owens, Benjamin M. J. (Public Library of Science, 2012)
Members of the Interferon Regulatory Factor (IRF) family of transcription factors play an essential role in the development and function of the immune system. Here we investigated the role of IRF7 in the functional activation of conventional CD11c(hi) splenic dendritic cells (cDCs) in vitro and in vivo. Using mice deficient in IRF7, we found that this transcription factor was dispensable for the in vivo development of cDC subsets in the spleen. However, IRF7-deficient cDCs showed enhanced activation in response to microbial stimuli, characterised by exaggerated expression of CD80, CD86 and MHCII upon TLR2 ligation in vitro. The hyper-responsiveness of Irf7 (−/−) cDC to TLR ligation could not be reversed with exogenous IFNα, nor by co-culture with wild-type cDCs, suggesting an intrinsic defect due to IRF7-deficiency. Irf7 (−/−) cDCs also had impaired capacity to produce IL-12p70 when stimulated ex vivo, instead producing elevated levels of IL-10 that impaired their capacity to drive Th1 responses. Finally, analysis of bone marrow microchimeric mice revealed that cDCs deficient in IRF7 were also hyper-responsive to TLR2-mediated activation in vivo. Our data suggest a previously unknown function for IRF7 as a component of the regulatory network associated with cDC activation and adds to the wide variety of situations in which these transcription factors play a role.